Are you afraid of the dark? Ghost island [videorecording (DVD)] - Grabinski, BenDavid, 1983- (Paramount, 2023)
Four best friends and members of the Midnight Society get more than they bargained for when a fun summer vacation on a resort island turns into something sinister. They encounter genuine terror locked away in one of the rooms in their hotel, and try as they might to enjoy their vacation, the kids are pulled back into the mystery of the island's ghosts. This ultimately leads them to a terrifying and shocking revelation: many guests check in to room 13, but they never check out.